Test of lepton universality in b → sℓ+ ℓ- decays - Aaij, Roel; Bachmann, Sebastian; Borsato, Martino; Caspary, Rowina; Frau, Giulia; Günther, Paul André; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; Hu, Jiangqiao; Leverington, Blake; Marks, Jörg; Morgenthaler, Maurice Pierre; et al. (Physical review letters, 2023)
The first simultaneous test of muon-electron universality using B+→K+ℓ+ℓ− and B0→K*0ℓ+ℓ− decays is performed, in two ranges of the dilepton invariant-mass squared, q2. The analysis uses beauty mesons produced in proton-proton collisions collected with the LHCb detector between 2011 and 2018, corresponding to an integrated luminosity of 9 fb−1. Each of the four lepton universality measurements reported is either the first in the given q2 interval or supersedes previous LHCb measurements. The results are compatible with the predictions of the Standard Model.